NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PANGGIH MANTEN PADA UPACARA PERNIKAHAN ADAT JAWA (Studi Kasus Desa Tulung Itik Kecamatan Gunung Sugih Kabupaten Lampung Tengah) - Wulandari, Erlin; Jaenullah; Muhammad Saidun Anwar (Najah Bestari, 2024)
The Panggih Manten traditional ceremony is a local culture that is still preserved and maintained to this day, this is because it is a form of cultural acculturation. The aim of this research is to describe the value of religious education in the Panggih Manten tradition, describe the value of moral education in the Panggih Manten tradition, describe the value of worship education in the Panggih Manten tradition. This research uses a qualitative field research method with a phenomenological approach. The data collection technique uses observation, interviews and documentation. Inductive data analysis includes data reduction, data presentation, verification (conclusion). From the research results, it has been found (1) the value of aqidah education in the mijil, tanem jero, and balangan gantal (believing in the destiny of Allah SWT) processions. (2) the value of moral education, the procession of wiji dadi (responsibility, respect and loyalty towards one's partner), sinduran (filial piety towards parents, sincerity, courage), dulangan (love and respect for one's partner), sungkeman (respect and devotion to others old), (3) the educational value of worship includes the process of kacar kacur (responsibility), dulangan (serving one's partner, providing for one's life), sungkeman (devotion to one's parents).